Second Assessment of Climate Change for the Baltic Sea Basin - BACC II Author Team, The (Regional Climate Studies, 2015)
Earth System Sciences; Atmospheric Sciences; Baltic Sea; Environmental Impacts; Regional Climate Change; Regional Climate Projections